Corporate takeovers and their implications for employees and the business world - Kerti, N. G. N. Renti Maharaini; Yurikosari, Andari (International Journal Labs, 2024)
This paper describes the legal framework surrounding expropriation in Indonesia and the implications this has for key stakeholders, including workers, the business world, and consumers. The research method used in this paper is normative legal research, relying on secondary data from literature and legal sources. The collected data is analyzed qualitatively, and conclusions are drawn through deductive reasoning. The study provides insights into how current regulations impact employment, business operations, and consumer rights. This research adds value by providing a legal analysis that can inform policymakers, legal professionals, and businesses on how to navigate the complexities within Indonesia's legal system.